Rodzina jako wartość w prasie społecznej lat 80. (na przykładzie "Magazynu Rodzinnego" z roku 1989) = Family as a value in the 80`s social Press (based on "Magazyn Rodzinny" from 1989) - Idzikowska, Magdalena (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aim of the analysis is to determine how family was evaluated in the social press in the 80`s, as well as which values connected with family life were dominating and being promoted at that time. The analyzed press texts valuating the family and home, derive from the 1989 annual magazine "Magazyn Rodzinny", which was published between 1974 and 1991.
Keywords: "Magazyn Rodzinny" - czasopismo; czasopiśmiennictwo; wartość; rodzina; print media; values; family